Assessing the performance of citrus industry in Kasibu, Nueva Viscaya, Philippines the case of farmers and traders of the Malabing Valley Agri-Trading Center - Antonio, Lyca Regina F.; Cruz, Mar B.; Madamba, Jeanette Angeline B.; Williams, Jimmy B. (2011)
Citrus has been identified as one of the top high-value crops in the Philippines, with the Cagayan Valley as one of the major citrus-producing regions, to which Kasibu, Nueva Vizcaya, belongs. This paper presents the status, issues, and opportunities of key players in the citrus industry of the Malabing Valley of Kasibu, where citrus production is concentrated. The study framework, through surveys, key informant interviews, and secondary sources of information included a descriptive analysis of the socio-demographic profile and the farming and trading operations and practices of key players within the overall industry structure. SWOT and cost and return analyses were used to assess current industry performance, giving rise to identification of citrus industry problems and prospects from which recommendation were formulated and offered. Twenty-three (23) citrus farmers, 7 farmer-traders, and 4 traders were interviewed based on the referral method. The actual field survey was conducted from December 2010 to January 2011. Results uncovered that of the three citrus fruit crops grown in Kasibu, namely, calamondin oranges, mandarin (Satsuma and Ponkan), and pomelos, mandarin constitutes majority of total average production volume per harvesting season. Findings further revealed that citrus farming is profitable in Kasibu, and many are encouraged to establish citrus orchards because of low entry barriers and less competition among farmers. On the other hand, there is a high degree of competition among traders. Farmers have the greatest contributed value to the products, but traders benefit most from the value-adding process. Several recommendations were also put forward to further sustain and improve the performance of Kasibu citrus supply chain actors.
Keywords: Citrus fruit industry